Green Human Resource Management and Environmental Sustainability: A Bibliometric Analysis and Systematic Literature Review - Mohamad Trio Febriyantoro; Wahyudi Henky Soeparto (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The growing urgency of environmental sustainability has positioned Green Human Resource Management (GHRM) as a pivotal research domain in organizational and management studies. This study presents a comprehensive bibliometric analysis and systematic literature review (SLR) of GHRM research published in Scopus-indexed journals, drawing upon a corpus of 50 peer-reviewed articles spanning 2016 to 2025. Using bibliometric indicators—including publication trends, citation analysis, keyword co-occurrence, and authorship patterns—alongside a thematic synthesis of study findings, this paper maps the intellectual landscape of GHRM scholarship. The analysis reveals an accelerating growth in GHRM publications post-2020, driven by increasing regulatory pressures and the global sustainability agenda. Four dominant research clusters are identified: (1) GHRM practices and employee green behavior; (2) GHRM and organizational environmental performance; (3) mediating and moderating mechanisms in GHRM–outcome relationships; and (4) sector-specific and contextual applications of GHRM. The AMO (Ability–Motivation–Opportunity) framework dominates theoretical discourse, while PLS-SEM predominates methodologically. Research concentrates in manufacturing and hospitality sectors in developing economies, particularly Asia and the Middle East. Critical gaps include insufficient longitudinal designs, limited cross-cultural analyses, and the underexplored intersection of GHRM with digital transformation. This paper contributes a comprehensive research roadmap for future GHRM scholarship and offers actionable implications for HR practitioners integrating sustainability into human capital strategies.